Modeling Coast Salish landscape/seascape use and territory with GIS - Morin, Jesse; Ritchie, Morgan; Blake, Michael; Hunt, Allison (Frontiers in Environmental Archaeology, 2025)
In this paper we use Least Cost Analysis (LCA) and GIS to model site catchments for villages from two Coast Salish tribes—Tsleil-Waututh and Sts'ailes. Here, we use Tobler's Hiker Function to model travel by land and develop a cost raster for travel by water in canoes. This model is then used to describe the site catchments for a number of villages. Comparison of the LCA model with recorded resource use patterns and modern hiking and canoeing times suggest that the model accurately describes traditional landscape and seascape use. The shape and size site catchments emphasize the importance of canoe travel in structuring Coast Salish daily foraging radii (~13 km). The large size site catchments of individual villages indicates that even one centrally-placed village could have exploited much of the tribal territory on a near-daily basis. Further, we find correspondence between our LCA modeled use areas and observed use areas, and the extent of each tribes' respective territory, indicating that the model is accurate in predicting past use areas, and that such use areas closely reflect the metes and bounds of a tribes' territory.